2021
DOI: 10.3389/fonc.2021.691705
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 Derived From Myeloma Associated Myeloid Cells Promotes TNFSF13B/TNFRSF13B-Dependent Proliferation and Survival of Myeloma Cells

Abstract: Multiple myeloma (MM) is a lethal hematological malignancy characterized by abundant myeloid cells in the microenvironment that fuel tumor progression. But the mechanism by which myeloid cells support myeloma cells has not been fully explored. We aimed to examine their effect on bone marrow cells of MM patients by scRNA-seq transcriptome analysis and reveal a high-resolution gene profile of myeloma cells and myeloma-associated myeloid cells. Based on correlation analysis of integrated scRNA-seq and bulk RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Myeloid-derived S100A9 can produce TNFSF13B through myeloid cells, neutrophils, and macrophages, and the enhanced TNFSF13B signal can activate the NF-κB pathway, thereby promoting plasma cell proliferation. 41 Additionally, the S100A8/S100A9 protein produced by bone marrow neutrophils and monocytes regulates myeloma progression by promoting megakaryocyte expansion and angiogenesis. 42 However, it remains unclear whether plasma cells with high expression of S100A9 impact tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid-derived S100A9 can produce TNFSF13B through myeloid cells, neutrophils, and macrophages, and the enhanced TNFSF13B signal can activate the NF-κB pathway, thereby promoting plasma cell proliferation. 41 Additionally, the S100A8/S100A9 protein produced by bone marrow neutrophils and monocytes regulates myeloma progression by promoting megakaryocyte expansion and angiogenesis. 42 However, it remains unclear whether plasma cells with high expression of S100A9 impact tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…It encodes BAFF (B-cell activating factor), a cytokine in the TNF ligand family that plays an important role in B cell development and activation [34]. TNFSF13B provides survival signalling to B cells by binding to two receptors, TNFRSF13B and TNFRSF13C, which initiate the activation of non-canonical NF-κB pathways [35]. It has been found that TNFRSF13B binding is critical for activation of the canonical NF-κB pathway [36].…”
Section: Discussionmentioning
confidence: 99%
“…As observed by experts, the activation of adenosine monophosphateactivated kinase (AMPK) partially mediates the tumor-promoting effect of MDSC in mice (90). Additionally, the production of S100A9, a calcium-binding protein that stimulates the secretion of TNF-a, IL-6, and IL-10 through toll-like receptor 4 (TLR4)-mediated autocrine signaling, by MDSCs in the tumor microenvironment (TME) attracts myeloma cells (91) and fosters their growth by activating the canonical nuclear factor-kappa B(NF-kB) pathway (92). MDSCs indirectly affect MM cells' survival through the modulation of nutrient availability, secretion of soluble factors, and the expression of cell surface inhibitory molecules.…”
Section: Myeloid-derived Suppressive Cellsmentioning
confidence: 99%